STUDY OF STATIC ELECTRICITY CHARGE ACCUMULATION ON SURFACE OF FLUOROPOLYMER-4 PRODUCTS USING VIBRATING CAPACITOR METHOD - H. А. Vershina; A. L. Zharin; A. K. Tiavlovsky (Наука и техника)
The paper presents investigations of processes pertaining to surface charge accumulation and running of fluoropolymer-4 products using vibrating capacitor method. Modification of a measurement technique allowing to register distribution of dielectric surface potential without disturbance of the surface charged state has been described in the paper. The paper contains graphics of spatial distribution of surface potential of fluoropolymer-4 products after various treatments. The paper reveals that thermal treatment (tempering) reduces static characteristics of fluoropolymer-4.